A novel organic-inorganic hybrid SiO2@DPP for the fire retardance of polycarbonate. (August 2018) - Wei, Yun-Xia; Deng, Cong; Zhao, Ze-Yong; Wang, Yu-Zhong
Abstract: To enhance the fire retardance of polycarbonate (PC), a novel organic-inorganic hybrid particle containing phosphorus and silicon (SiO2 @DPP) was synthesized through a facile hydrothermal reaction. Different measurements verified that the SiO2 @DPP was prepared successfully. After incorporation of the SiO2 @DPP into PC, it was found that the flame retardancy of PC was greatly affected by only small amount of SiO2 @DPP. The PC containing only 0.8 wt% SiO2 @DPP passed the UL-94 V-0 rating in vertical combustion test and had the limiting oxygen index (LOI) of 29.3%. Moreover, the dripping behavior of PC was also restricted in this case. In cone calorimetry test, the peak heat release rate (PHRR) and the peak smoke production rate (PSPR) of PC were correspondingly remarkably reduced by 41.6% and 15.4% in the presence of only 0.8 wt% SiO2 @DPP. Moreover, the flame-retardant mechanism of the SiO2 @DPP was also investigated in detail through different measurements. The results demonstrated that the phosphorus-containing substances and SiO2 left in the condensed phase and some structures containing phosphorus in gaseous phase had great contribution to excellent fire retardance of PC/SiO2 @DPP. All these results demonstrate that the SiO2 @DPP is an efficient organic-inorganic hybrid material for preparing fire-retardance PC. Highlights: A novel organic-inorganic hybrid SiO2 @DPP for polycarbonate. The excellent flame retardancy of polycarbonate was achieved at 0.8 wt% SiO2 @DPP. The flame-retardant mechanism of PC/SiO2 @DPP was proposed.